Low level of dark personality traits in transgender people and their relationships with resilience - Mateja, Agnieszka; Gawda, Barbara (Frontiers in Psychiatry, 2025)
IntroductionIn addition to anxiety disorders and depressive symptoms, transgender people are also shown to have pathological personality profiles. These patterns are due to functioning under chronic stress, exposure to discrimination, victimization, the inability to affirm gender identity, and insufficient social support. The internalized transphobia predisposes transgender individuals to psychological decompensation. The study aims to assess Dark Personality Trait among transgender individuals and to establish the relationships between Dark Tetrad traits and resilience.Materials and MethodsThe Dark Tetrad (narcissism, psychopathy, Machiavellianism, sadism) was assessed using The Short Dark Tetrad Scale (SD4-PL). Resilience was measured using The Resilience Measurement Scale (SPP-25) questionnaire. The dimensions of psychological resilience were also evaluated, including perseverance, determination in action, openness to new experiences, sense of humor, personal competence in coping, tolerance of negative emotions, tolerance for failure, viewing life as a challenge, optimism, and the ability to mobilize in difficult situations. In the statistical analysis, a Multivariate Analysis of Covariance (MANCOVA) was conducted. Correlations between dark personality traits in the transgender and cisgender groups were compared using Fisher’s z-test.ResultsThe study results indicate a slightly lower level of narcissism and Machiavellianism in transgender women compared with cisgender women, and a slightly increased level of sadism in all men, regardless of whether they are transgender or cisgender. No differences were observed between the transgender and cisgender groups in terms of dark personality traits. Transgender individuals exhibited significantly lower level of general resilience than cisgender individuals.ConclusionsThe results of participants from the transgender group indicate lower level of dark personality traits. Observed differences in dark personality traits are related to gender and are independent of transgenderism. Psychological resilience provides a subtle protective function against the development of dark personality traits.